2023
DOI: 10.3390/biomedicines11061719
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Differentially Expressed in Actinic Keratosis and Healthy Skin Scrapings

Abstract: Actinic keratosis (AK) is a carcinoma in situ precursor of cutaneous squamous cell carcinoma (cSCC), the second most common cancer affecting the Caucasian population. AK is frequently present in the sun-exposed skin of the elderly population, UV radiation being the main cause of this cancer, and other risk factors contributing to AK incidence. The dysregulation of microRNAs (miRNAs) observed in different cancers leads to an improper expression of miRNA targets involved in several cellular pathways. The TaqMan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“… 19 However, there have been limited studies performed in the setting of SCC or their precursor lesions such as AK and IEC. 20 , 21 Moreover, we still have very limited understanding on natural history of AK formation. Here, we performed a global miRNA expression profiling in SCC and its associated precursor lesions with the goal to find potential biomarkers and the role of miRNA in SCC development.…”
Section: Discussionmentioning
confidence: 99%
“… 19 However, there have been limited studies performed in the setting of SCC or their precursor lesions such as AK and IEC. 20 , 21 Moreover, we still have very limited understanding on natural history of AK formation. Here, we performed a global miRNA expression profiling in SCC and its associated precursor lesions with the goal to find potential biomarkers and the role of miRNA in SCC development.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Nguyen et al [19] summarized how miR-29s can have opposite roles in different human cancers, acting as either oncogene or tumor suppressors. Chiantore et al [20] defined a miRNA signature in actinic keratosis, a skin condition that can lead to cancer, that may affect the pathways involved in tumor development. De Almeida et al [21] reported the most relevant findings on the epigenetic features of uterine leiomyosarcomas and endometrial stromal sarcoma, two rare and aggressive cancers.…”
Section: Mirnas In Human Diseasesmentioning
confidence: 99%